A Patient with Dermatomyositis Developing Steroid Induced Myopathy: A Case Report (Journal of Dhaka Medical College, 2016)
Dermatomyositis is not a very uncommon disease affecting skin and muscles. Some varieties have atypical presentations and early diagnosis is pivotal to the effective management as it has significant morbidity and mortality including malignancy. Corticosteroids and other immunosuppressive is the mainstay of treatment; however, it should also be aimed to reduce the complications of steroid therapy as there is a possibility of steroid induced myopathy where withdrawal of steroid with introduction of other immunosuppressive drug is promptly warranted. Here, we presented a 60 year old lady with dermatomyositis who developed steroid induced myopathy.J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 156-159